Evaluation of surface roughness, cytotoxicity, and antibacterial effects of silver nanoparticle coating on copper nickel titanium orthodontic arch wires - in vitro study - Daphane Anishya; Ravindra K. Jain (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Surface roughness of arch wires directly impacts their corrosion behavior, friction resistance, and plaque accumulation, which may hinder tooth movement and lead to dental caries. OBJECTIVES: The study aims to synthesize vanillin-mediated silver nanoparticles (AgNPs), characterize them, assess surface roughness and cytotoxicity of arch wires after silver nanoparticle coating, and test their antibacterial properties. MATERIALS AND METHODS: Nine copper-nickel-titanium arch wires (CuNiTi) were cut into equal pieces. Three were sent for surface roughness assessment, three for cytotoxicity, and three for antibacterial testing. Dip coating of wires was done using the sol-gel thin film method. The surface roughness (Ra) before and after coating was evaluated using scanning electron microscopy and atomic force microscopy. Cytotoxicity testing was done with a (3- (4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay using gingival fibroblasts. Statistical analysis was done using SPSS software. Antibacterial activity against S. mutans was tested using the Agar-well diffusion method. RESULTS: The CuNiTi wires were coated successfully, and the coating appeared homogeneous. The mean Ra after coating (297.3+/- 30.4 nm) was significantly less than that before coating (339.7+/-49.2 nm). AgNPs showed minimal cytotoxicity against human gingival fibroblasts at different concentrations. Optical microscopy showed over 90% viability between 12.5 and 100 µg/ml. At 100 µg/ml, only 80% of cells remained viable. AgNP coating is biocompatible at concentrations up to 75 µg/ml. There was a significant intergroup difference in the zone of inhibition (antibacterial activity) noted with higher values in noncoated wires. (P value <0.007). CONCLUSION: AgNPs coated on CuNiTi arch wires showed reduced surface roughness and minimal cytotoxic effects on human gingival cells and good antibacterial activity against S. mutans compared to noncoated arch wires.